2002
DOI: 10.1177/026666602321036650
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology in University Libraries in Karnataka

Abstract: Examines the results of a survey of the availability and use of information technology in the libraries of the University of Mysore, Karnatak University, Bangalore University, Gulbarga University, Mangalore University and Kuvempu University in Karnataka State, India. Attempts to reflect how the use of IT has impacted on the overall use of the library collections by users. Covers the use of computers, networks, electronic mail, online information retrieval, CD-ROM, facsimile transmission, personal computers (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Information technology is a collective term used for various technologies involved processing and transferring information (Nyamboga & Kemparaju, 2002). Technology allows people to work quickly and assist in making a decision by considering more data.…”
Section: Information Technology Applicationmentioning
confidence: 99%
“…Information technology is a collective term used for various technologies involved processing and transferring information (Nyamboga & Kemparaju, 2002). Technology allows people to work quickly and assist in making a decision by considering more data.…”
Section: Information Technology Applicationmentioning
confidence: 99%
“…Databases, OPACs and internet are being used and both the librarians and students have adapted to the use of IT very well. As a result of doing a research in six university libraries in Karnataka (India), Nyamboga and Kemparaju (2002) concluded that these libraries still lag behind some other Indian universities in the application of IT, but the introduction of internet access is an important step forward. Regardless of a not very good picture of IT application in Karnataka, finally, they suggested that with basic IT literacy, library users and staff are able to retrieve more up‐to‐date information that supplements what they get from printed information sources, thereby increasing the efficiency and effectiveness of the academic libraries as well as helping to bring the whole institution into the information age.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information technology is the collective [umbrella] term for various technologies involved in processing and transmitting information that may include computing, telecommunications and microelectronics (Nyamboga and Kemparaju, 2002). According to the American Library Association (1983, p. 183), it has been defined as “the application of computers and other technologies to the acquisition, organization, storage, retrieval, and dissemination of information”.…”
Section: Information Technology Definitionmentioning
confidence: 99%
“…As a result of doing a research in six university libraries in Karnataka (India), Nyamboga and Kemparaju (2002) concluded that these libraries still lag behind some other Indian universities in the application of information technology, but the introduction of internet access is an important step forward. Regardless of a not very good picture of information technology application in Karnataka, finally, they suggested that with basic information technology literacy, library users and staff are able to retrieve more up‐to‐date information that supplements what they get from printed information sources, thereby increasing the efficiency and effectiveness of the academic libraries as well as helping to bring the whole institution into the information age.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation